Differential pathways to disordered eating for immigrant and native adolescents in Taiwan - Duan-Rung Chen; Li-Yin Lin; Brianna Levin (Journal of Eating Disorders, 2023)
Plain English summary This study fills the gap in the literature on disparities in disordered eating and factors associated with disordered eating among immigrant adolescents in Taiwan. To our knowledge, this is the first study focusing on disordered eating among immigrant adolescents in Taiwan. The unique contribution of this research is to elucidate the different pathways leading to disordered eating for native and immigrant adolescents. In native adolescents, weight-teasing by family members but not by friends was indirectly related to disordered eating through psychological distress. In adolescents with an immigrant background, weight-teasing by friends was indirectly associated with disordering eating through psychological distress. Additionally, weight overestimation is a unique risk factor directly and indirectly through psychological distress related to disordered eating for immigrant adolescents. As a highly Westernized country, the Taiwanese’s mainstream ideal body shape is “thinness.” Substantial social discrimination against obese adolescents regarding peer acceptance and sexual attraction may put immigrant adolescents at an increased risk of experiencing body dissatisfaction, psychological stress, and eating disorder symptoms due to their minority status, struggling to adapt to a social environment different from their parents, and wanting peer acceptance. The study urges the need for school-based prevention programs to improve immigrant students’ mental health.